Mydriatic efficacy of topical phenylephrine and tropicamide combination vs tropicamide in screening for retinopathy of prematurity (ROP) – An RCT - Camina Andrews; Shubashree Karat; Winston Padua; Saudamini V Nesargi; Suneetha Nithyanandam; Shalini Butola (Kerala Journal of Ophthalmology)
Introduction: Screening for ROP and its severity require optimum pupillary dilatation. Mydriatics that allow good dilatation often have systemic side effects. Topical tropicamide is considered safest but does not dilate pupils optimally. A combination of phenylephrine and tropicamide is a good mydriatic but has adverse effects. The study aims to compare the mydriatic efficacy of phenylephrine (P 2.5%) plus tropicamide (T 0.4%) versus tropicamide (T 1%) alone for ROP screening. Methods: Preterm neonates due for ROP screening were randomized to one of the two groups. One drop was instilled in the eye thrice every 15 mins. Pupillary diameter was recorded as a primary outcome measure using the Schirmer’s strip at baseline, 15, 30, and 45 minutes after drop instillation. Oxygen saturation, heart rate, and respiratory rate were measured at similar intervals. Adverse effects like apneas, vomiting, and feed intolerance were documented. Ophthalmologist comments on the visibility of different retinal zones were also recorded. Data were analyzed by t-test and Chi-square test as appropriate. Results: Fifty-four preterm babies were included (27 in each group). The birth weight (1130 ± 300g, 1220 ± 460 g) and gestation (34.40 ± 2.26 and 34.74 ± 3.24) weeks were similar in both groups. The pupillary size after 45 minutes in group 1 (7.56 ± 1.12 mm) was significantly greater (P < 0.001) than that of group 2 (5.92 ± 0.90 mm). The visibility of retinal zones was better in group 1 compared to group 2, which was statistically significant (P < 0.01). There was no significant difference between the two groups in saturation, heart rate, and respiratory rate at 30 mins and 45 mins. Conclusion: A combination of phenylephrine and tropicamide is a more effective mydriatic with no increase in adverse effects.